The role of the parties in mangrove ecosystem recovery in Juntinyuat Coast, West Java, Indonesia - Muhamad Hasan; Dolly Priatna; Yossa Istiadi (Indonesian Journal of Applied Environmental Studies, 2022)
Coastal abrasion is a problem that needs to be addressed thoroughly. If not properly managed, coastal abrasion can lead to other environmental issues, such as damage to mangroves and coastal ecosystems. The local government is actively carrying out mangrove ecosystem restoration program to conserve the coastal ecology by involving related agencies, industries, and the community surrounding the Juntinyuat coastal area. The focus of this research is to find out the planning, implementation, and monitoring carried out in relation to the restoration of the mangrove ecosystem based on the involvement of the parties in overcoming coastal abrasion on the coast of Juntinyuat, Indramayu Regency, West Java. Data were collected by conducting observations, interviews, and documentation to the community and the parties involved in restoring the mangrove ecosystem on the Juntinyuat coast. The results showed that mangrove ecosystem damage in the coastal area of Juntinyuat generates a high level of abrasion. The damage caused by abrasion threatens settlements, ponds, and agricultural land, as well as threatens the gas and oil pipelines of Pertamina Gas in the West Java operation area (Pertagas OWJA). There is a relationship between the critical condition of the mangrove ecosystem in the Juntinyuat coastal area and the initiation of efforts to restore the mangrove ecosystem. The initiation of mangrove ecosystem restoration arose from the critical condition of mangroves, which necessitates careful planning to restore damaged mangrove conditions. Related parties concerned with the preservation of the mangrove ecosystem subsequently coordinate to plan the mangrove ecosystem restoration program on the Juntinyuat coast. The mangrove ecosystem restoration was conducted after an initial survey in mid-2014. The role of the parties in planning, implementing, and monitoring the restoration of the mangrove ecosystem is running well and maximally with a clear division of duties and responsibilities. Currently, the results of the restoration of the mangrove ecosystem on the Juntinyuat coast can be felt together with the denser mangrove cover, reducing the abrasion impact, and making it a mangrove ecotourism area. In the future, it is necessary to form a coordinating team for the strategy of mangrove ecosystem management at the regency and sub-district levels to synergize policies and programs for managing mangrove ecosystems. Empowerment activities need to be carried out intensively to encourage a change in the role of mangrove management.